If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2b-4=-7
We move all terms to the left:
2b-4-(-7)=0
We add all the numbers together, and all the variables
2b+3=0
We move all terms containing b to the left, all other terms to the right
2b=-3
b=-3/2
b=-1+1/2
| 16=-16t^2+179t+0 | | 6+5x3=x | | 6(x+5)=5(x-5)+x | | (7+x/2)=14 | | 13x+4(5–3x)=1 | | 25=14+b | | 3x-5=x2 | | 12.x=156 | | 8x^2+3x-2=5 | | 128/4=m | | -6t-5=t-5 | | 1224=3.z | | x/5+2/3=11/3 | | 306-42=p | | 4x+2+3x-7=58 | | 3(x+3)+5=3x+7 | | -4-7f=-6f-3 | | x-(0.25x)=1,000 | | 20=7y+-y | | –5(7+x)=x–39 | | -14+n=5 | | N-246=605-(4x28) | | -0.9(h-3)=-0.99 | | 4x=2x+38 | | 8n−(6n+5)=9 | | 2(y-3)+2=8 | | -4(2x+5)+2x+3=−-11 | | -4=u/2-7 | | 10b+18= 28 | | 3x+3-6x+3=-3x+6 | | -6y-2=-4(y+2) | | -76=-3b49 |